Tailored phage cocktail with resistance management for controlling Dickeya solani in potatoes - Sabri, Miloud; Mektoubi, Khaoula; Habbadi, Khaoula; Cara, Orges; El Handi, Kaoutar; De Stradis, Angelo; Elbeaino, Toufic (Frontiers in Microbiology, 2026)
Dickeya solani, the causal agent of soft rot and blackleg diseases in potatoes, is responsible for substantial economic losses worldwide, with no effective environmentally acceptable chemical control measures available. Bacteriophage-based biocontrol represents an environmentally sustainable alternative to chemical treatments; however, the rapid emergence of resistant bacterial strains remains a major limitation to their efficacy. In this study, we developed a phage cocktail consisting of three bacteriophages (LMST, PDS1, and PDS2) through a rational, sequential isolation strategy to effectively target D. solani and its emerging phage-resistant strains. High-throughput sequencing and genomic analyses revealed that LMST, PDS1, and PDS2 possess double-stranded DNA genomes of 153,878, 254,449, and 133,665 bp, respectively, and lack genes associated with lysogeny, virulence, or antibiotic resistance. Transmission electron microscopy (TEM) analyses revealed a myovirus-like morphology and confirmed efficient replication of the phages on D. solani cells. Host range assays demonstrated that the phages were specific to D. solani strains, with LMST additionally infecting D. fangzhongdai, while thermal stability tests indicated that all three phages maintained infectivity across a broad temperature range (−20 °C to 60 °C), collectively supporting their potential as suitable biocontrol agents. Phylogenetic analyses classified LMST and PDS1 within the genera Limestonevirus and Salmondvirus, respectively, whereas PDS2 represented a highly divergent lineage, expanding the anti-Dickeya phage repertoire. Turbidity assays revealed that the phage cocktail more effectively suppresses D. solani growth than individual phages and substantially reduces the development of phage resistance. Furthermore, preventive and curative applications of the phage cocktail resulted in 68.75 and 59% reductions in D. solani-induced symptom severity in potato tubers, respectively. This study demonstrates that a rationally designed phage cocktail can significantly control D. solani infections while mitigating the emergence of phage-resistant strains.